INOVASI AKAD CASH WAQF LINKED DEPOSIT (CWLD) UNTUK SINERGI FUNGSI SOSIAL DAN KOMERSIAL BANK SYARIAH - Sihite, Nadya; Husni Kamal; Sayuti, Ahmad; Safrina, Eka; Afdhilah, Nur (STAI La Tansa Mashiro, 2025)
Abstrak This study reviews the innovation of Islamic banking products, namely Cash Waqf Linked Deposit (CWLD), as a solution for productive and transparent waqf fund management. The main objective of the research is to examine the legal basis, operational mechanism, as well as the potential and challenges of CWLD development in Indonesia. The method used is library research and descriptive analysis. The results show that CWLD is able to unite the synergy of social and commercial functions of Islamic banks through clear regulations, appropriate sharia contracts, and innovative fund management mechanisms. This product has great potential to expand public participation in cash waqf and support sustainable socio-economic development. Keywords: Cash Waqf Linked Deposited (CWLD), Waqf funds, Sharia innovation, Socio-economy